The Effect of Human Resources Development on the Performance of State Civil Servants (ASN) - Martini Martini; Henson Enjein Manurung; Januar Ida Wibowati; Endang Rahayu (Almana : Jurnal Manajemen dan Bisnis, 2022)
Natural Resource Development will provide benefits to state civil servants (ASN) at the Ministry of Religion of South Sumatra Province. Agencies will get benefits in the form of increasing performance, productivity, elasticity, and flexibility to adapt to an ever-changing environment. The purpose of this research is "to find out and analyze whether the development of human resources affects the performance of the State Civil servants (ASN) at the Ministry of Religion of South Sumatra Province". This research method uses quantitative research with explanatory research, meaning that research is conducted to see the relationship between variables with the aim of testing hypotheses. This method is expected to explain phenomena based on the data and information obtained. The population and sample in this study are only employees with civil servant status who have participated in human resource development programs. The results of this study indicate that based on the Determination Coefficient Test shows a strong relationship between human resource development and performance. Based on the results of the hypothesis test, the researcher can conclude that the human resource development variable has a significant positive or unidirectional influence on employee performance at the Ministry of Religion of South Sumatra Province.